1994
DOI: 10.1007/bf01324800
|View full text |Cite
|
Sign up to set email alerts
|

The effect of financing decisions on the choice of manufacturing technologies

Abstract: Abstract. This paper demonstrates the importance of jointly considering financing and technology choices when making manufacturing investments. We show that considerable value can be added to investments through financing decisions, and that the gains due to financing are sensitive to technology choice. A model of financing and technology choice is presented that considers differences in cost structure and product flexibility, and applies it to an example involving flexible manufacturing systems (FMSs). Three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…Except for a numerical analysis in Lederer and Singhal (1994), there is no formal treatment of the two-product firm in the literature, therefore, the two-product analysis is a distinct contribution of our research.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Except for a numerical analysis in Lederer and Singhal (1994), there is no formal treatment of the two-product firm in the literature, therefore, the two-product analysis is a distinct contribution of our research.…”
Section: Resultsmentioning
confidence: 99%
“…An analytical characterization of the two-product firm is entirely new to this literature. The only paper to focus on flexible technology is Lederer and Singhal (1994), whose main focus is to study the joint financing (optimal mix of debt and equity) and capacity investment problem in a single-product, multi-period setting under the assumption of a perfectly competitive credit market. In a numerical example, they analyze the capacity-pooling benefit of flexible technology in a multi-product firm.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…Contributions on the link between industrial decisions and financial structure may be found in Lederer and Singhal (1994), in Leland (1998) Leland (1998) digs the same topic raised in the seminal paper of Jensen and Meckling (1976). Unlike Leland (1998), Mauer and Sarkar (2005) emphasize the inefficiency of debt.…”
Section: Introductionmentioning
confidence: 93%
“…However, investing in a flexible technology with a high c t is too risky and the equityholders choose zero flexibility. 26 The comparison with respect to the unlevered firm is summarized in the following proposition: 2 6 This is consistend with the comparative statics of (26.2) and (26.3). That is, …”
Section: Proposition 4 the Ex-ante Value Of The Firm Ismentioning
confidence: 99%
See 1 more Smart Citation